2010
DOI: 10.1186/1756-9966-29-160
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative factor decreases Akt phosphorylation and alters gene expression via CKAP4 in T24 bladder carcinoma cells

Abstract: BackgroundUrinary bladder cancer is a common malignancy worldwide, and outcomes for patients with advanced bladder cancer remain poor. Antiproliferative factor (APF) is a potent glycopeptide inhibitor of epithelial cell proliferation that was discovered in the urine of patients with interstitial cystitis, a disorder with bladder epithelial thinning and ulceration. APF mediates its antiproliferative activity in primary normal bladder epithelial cells via cytoskeletal associated protein 4 (CKAP4). Because synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(70 citation statements)
references
References 37 publications
5
64
1
Order By: Relevance
“…It was reported that CKAP4 plays important roles in several cellular processes, including endoplasmic reticulum anchoring 18 and morphology determination 19, regulation of Dicer function 20, cell proliferation 21 and tumour migration 22, 23. Knockdown of CKAP4 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that CKAP4 plays important roles in several cellular processes, including endoplasmic reticulum anchoring 18 and morphology determination 19, regulation of Dicer function 20, cell proliferation 21 and tumour migration 22, 23. Knockdown of CKAP4 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge to date, there is evidence linking the CKAP4 gene to tumor growth in patients with bladder cancer and cervical carcinoma. 8,9 Our recent work indicates that CKAP4 is a prognostic marker in patients with intrahepatic cholangiocellular carcinoma and is clinicopathologically associated with tumor progression and metastasis. 14 To our knowledge, systematic investigation of the prognostic significance of CKAP4 in HCC has not been reported to date, especially with long-term follow-up and a large number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Recently, it has been identified as a cell surface receptor for tissue plasminogen activator and surfactant protein A, as well as antiproliferative factor. 3,[7][8][9] It has been shown that CKAP4 may inhibit the proliferation of bladder cancer cells by combining its ligand antiproliferative factor, whose mechanism may be related to the Wnt signaling pathway. Recent studies have shown that palmitoylation by DHHC2, a putative tumor suppressor, is required for CKAP4 trafficking from the endoplasmic reticulum to the plasma membrane and for its nuclear localization.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of Akt activity is considered to be an effective strategy for bladder cancer treatment (25). Bcl-2 is also a direct participant in the apoptotic pathway and has tumorigenic potential (18).…”
Section: Discussionmentioning
confidence: 99%